Best Practices and Lessons Learned for Action Research in eHealth Design and Implementation: Literature Review - Kira Oberschmidt; Christiane Grünloh; Femke Nijboer; Lex van Velsen (JMIR Publications, 2022)
BackgroundAction research (AR) is an established research framework to introduce change in a community following a cyclical approach and involving stakeholders as coresearchers in the process. In recent years, it has also been used for eHealth development. However, little is known about the best practices and lessons learned from using AR for eHealth development. ObjectiveThis literature review aims to provide more knowledge on the best practices and lessons learned from eHealth AR studies. Additionally, an overview of the context in which AR eHealth studies take place is given. MethodsA semisystematic review of 44 papers reporting on 40 different AR projects was conducted to identify the best practices and lessons learned in the research studies while accounting for the particular contextual setting and used AR approach. ResultsRecommendations include paying attention to the training of stakeholders' academic skills, as well as the various roles and tasks of action researchers. The studies also highlight the need for constant reflection and accessible dissemination suiting the target group. ConclusionsThis literature review identified room for improvements regarding communicating and specifying the particular AR definition and applied approach.